Poezje braci Grzymałowskich – casus długiego trwania konwencji sentymentalnej w wieku XIX - Samborska-Kukuć, Dorota (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2010)
Brothers: Walerian, Klemens and Julian Grzymałowski, the poets of Polish-Belorussian borderline are representatives of a long-lasting existence of sentimental style in a borderland literature at the 19th century. Although their poetry was described as worthless and epigonic, it consists very important elements of regional folklore important for retaining national identity in this area. The poetics inherited from sentimentalism served these enthusiasts of people to polish a local poetry up including its unique and exceptional character.